2020
DOI: 10.22541/au.159795391.12993390
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

COVID-19 in Children with Cancer: A single Low-Middle income center experience

Abstract: Background: Coronavirus disease-2019 (COVID-19) could be associated with morbidity and mortality in immunocompromised children. Objective: To measure the frequency of SARS-COV-2 infection among hospitalized children with cancer and detect the associated clinical manifestations and outcomes. Methodology: A prospective non-interventional study including all hospitalized children with cancer conducted between mid-April and mid-June 2020 in Ain Shams University hospital, Egypt. Clinical, laboratory and radiologica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 13 publications
(14 reference statements)
0
4
0
Order By: Relevance
“…Clinical outcomes in immunocompetent children with COVID-19 are superior to adults and several mechanisms including lower angiotensin converting enzyme (ACE)-2 expression, enhanced immune tolerance, and fewer co-morbidities have been proposed as reasons for the discrepant outcomes 47 . These protective features may be minimized in some immunocompromised populations as ACE-2 can be overexpressed in some patients with IBD and systemic lupus erythematous (SLE) 48 , 49 .…”
Section: Introductionmentioning
confidence: 99%
“…Clinical outcomes in immunocompetent children with COVID-19 are superior to adults and several mechanisms including lower angiotensin converting enzyme (ACE)-2 expression, enhanced immune tolerance, and fewer co-morbidities have been proposed as reasons for the discrepant outcomes 47 . These protective features may be minimized in some immunocompromised populations as ACE-2 can be overexpressed in some patients with IBD and systemic lupus erythematous (SLE) 48 , 49 .…”
Section: Introductionmentioning
confidence: 99%
“…We screened a total of 2759 records after transferring the databases results without duplicates. We further assessed 61 full texts for eligibility which ended up with a total of 21 articles including 14 studies and additional seven studies following manual search procedures 7 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 (Figure 1 , Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Three of the four cases presented with an MIS-C-like picture (Sherif et al, 2021). On the other hand, studies conducted on cancer children with COVID-19 showed that these can be either asymptomatic (Ebeid et al, 2021) or symptomatic with mainly mild-to-moderate form of the illness (Hammad et al, 2021;Hamdy et al, 2021). The mortality rate was as low as 6.5% after the exclusion of septicemia and cancer progression in one study (Hammad et al, 2021) and almost the half in another one (Hamdy et al, 2021).…”
Section: Childrenmentioning
confidence: 91%
“…The younger age of the participating HCW with less likely accompanied comorbidities could be the reason behind this observation (El-Raey et al, 2021). Healthcare facility and contact with a confirmed COVID-19 case during work were the most common sources of infection for HCWs (Kassem et al, 2020;Abou-ElWafa et al, 2021;El-Raey et al, 2021;Mostafa et al, 2021). Interestingly, many healthcare workers admitted that they do not know exactly where they were infected (Abou-ElWafa et al, 2021;El-Raey et al, 2021).…”
Section: Introductionmentioning
confidence: 99%